Oral Questioning Skills In Teaching Mathematics: A Preliminary Study - Mahmud, Muhammad Sofwan; Zainal, Mohd Syazwan; Pa, Wan Ahmad Munsif Wan (The journal of contemporary issues in business and government, 2021)
Oral questioning is an essential element in the process of teaching mathematics. However, not much is known about what oral questioning skills are commonly used by mathematics teachers in teaching mathematics in primary schools. Thus, this study is qualitative takes the form of a case study of two study participants who have been selected using purposive sampling, conducted in a primary school in Negeri Sembilan. This study uses observation methods and field notes to collect data. The data obtained are analyzed using thematic and descriptive analysis to obtain information on the oral questioning skills used and the frequency of oral questions used by two mathematics teachers with different teaching experiences. The results show that these two mathematics teachers often use questioning in mathematics teaching, but that there is no significant difference between them in terms of frequency of the use of questioning. The study also found that both study participants used various oral questioning skills in teaching mathematics. This study is a preliminary study designed to enable general aspects of questioning skills in mathematics teaching to be identified and to guide future studies on oral questioning.